Extended effects of a wearable sensory prosthesis on gait, balance function and falls after 26 weeks of use in persons with peripheral neuropathy and high fall risk—The walk2Wellness trial - Oddsson, Lars I. E.; Bisson, Teresa; Cohen, Helen S.; Iloputaife, Ikechukwu; Jacobs, Laura; Kung, Doris; Lipsitz, Lewis A.; Manor, Brad; McCracken, Patricia; Rumsey, Yvonne; Wrisley, Diane M.; Koehler-McNicholas, Sara R. (Frontiers in Aging Neuroscience, 2022)
Background We recently reported that individuals with impaired plantar sensation and high fall risk due to sensory peripheral neuropathy (PN) improved gait and balance function following 10 weeks of use of Walkasins®, a wearable lower limb sensory prosthesis that provides directional specific mechanical tactile stimuli related to plantar pressure measurements during standing and walking (RxFunction Inc., Eden Prairie, MN, United States). Here, we report 26-week outcomes and compare pre- and in-study fall rates. We expected improvements in outcomes and reduced fall rates reported after 10 weeks of use to be sustained. Materials and methods Participants had clinically diagnosed PN with impaired plantar sensation, high fall risk (Functional Gait Assessment, FGA score < 23) and ability to sense tactile stimuli above the ankle at the location of the device. Additional outcomes included 10 m Gait Speed, Timed Up and Go (TUG), Four-Stage Balance Test, and self-reported outcomes, including Activities-Specific Balance Confidence scale and Vestibular Disorders Activities of Daily Living Scale. Participants tracked falls using a calendar. Results We assessed falls and self-reported outcomes from 44 individuals after 26 weeks of device use; 30 of them conducted in-person testing of clinical outcomes. Overall, improvements in clinical outcomes seen at 10 weeks of use remained sustained at 26 weeks with statistically significant increases compared to baseline seen in FGA scores (from 15.0 to 19.2), self-selected gait speed (from 0.89 to 0.97 m/s), and 4-Stage Balance Test (from 25.6 to 28.4 s), indicating a decrease in fall risk. Non-significant improvements were observed in TUG and fast gait speed. Overall, 39 falls were reported; 31 of them did not require medical treatment and four caused severe injury. Participants who reported falls over 6 months prior to the study had a 43% decrease in fall rate during the study as compared to self-report 6-month pre-study (11.8 vs. 6.7 falls/1000 patient days, respectively, p < 0.004), similar to the 46% decrease reported after 10 weeks of use. Conclusion A wearable sensory prosthesis can improve outcomes of gait and balance function and substantially decreases incidence of falls during long-term use. The sustained long-term benefits in clinical outcomes reported here lessen the likelihood that improvements are placebo effects. Clinical trial registration ClinicalTrials.gov, identifier #NCT03538756.